Drill and Practice Method to Improve Students’ Informatics Learning Outcomes - Putranto Argya Kuncara Jati; Endar Suprih Wihidayat; Yudianto Sujana (Universitas Pendidikan Ganesha, 2025)
Various instructional methods can be employed to achieve learning objectives. In vocational high schools (SMK), Informatics is one of the subjects taught to tenth-grade students and consists of both theoretical and practical activities. Learning methods that rely heavily on textbook-centered instruction often lead to student boredom and suboptimal learning outcomes. To address this issue, the drill and practice method was implemented. This study aims to analyze the implementation of the drill and practice method in improving students’ learning outcomes in Informatics. The research employed a classroom action research design with a descriptive quantitative approach. The research subjects consisted of 36 students. Data were collected from students and teachers through interviews, tests, observations, questionnaires, and documentation. Data analysis was conducted using qualitative methods, including data reduction, data presentation, and conclusion drawing with verification. The results indicate that the drill and practice method effectively improves students’ learning outcomes in Informatics. The delivery of theoretical material involved repeated explanations for each topic and subtopic, while practical activities were also conducted through repeated exercises for each topic and subtopic. As a result, students demonstrated improved understanding of basic C programming concepts.